2016
DOI: 10.4168/aair.2016.8.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Response to Nonallergenic Irritants in Children With Allergic and Nonallergic Rhinitis

Abstract: PurposeNonallergenic irritants can aggravate the symptoms of rhinitis. We investigated the clinical responses of children with allergic rhinitis (AR) and nonallergic rhinitis (NAR) to nonallergenic irritants, and identified factors associated with these responses.MethodsChildren with chronic rhinitis (n=208) were classified as having AR or NAR based on the presence of aeroallergen-specific IgE. Healthy controls (n=24) were recruited for comparison. The Allergic Rhinitis and its Impact on Asthma (ARIA) guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Our findings indicate that NAR patients with decreased nasal patency, similar to AR patients, had more severe nasal symptoms and increased small airway resistance. This result corresponds with previous studies, which showed that NAR is associated with less severe nasal symptoms than AR, and that the severity of nasal symptoms is associated with the risk for asthma . This may explain the relationship of more severe rhinitis and decreased nasal patency with increased small airway resistance, even in subjects with NAR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings indicate that NAR patients with decreased nasal patency, similar to AR patients, had more severe nasal symptoms and increased small airway resistance. This result corresponds with previous studies, which showed that NAR is associated with less severe nasal symptoms than AR, and that the severity of nasal symptoms is associated with the risk for asthma . This may explain the relationship of more severe rhinitis and decreased nasal patency with increased small airway resistance, even in subjects with NAR.…”
Section: Discussionsupporting
confidence: 91%
“…However, allergic sensitization accounts for only 38% of the association between AR and asthma . Moreover, there seems to be an association between asthma and non‐allergic rhinitis (NAR), although the relationship between NAR and asthma cannot be fully explained by local IgE‐mediated processes, and there appear to be other important immunological, morphological, or pathophysiological factors . Although AR and NAR have different pathophysiologies, each increases the risk for asthma …”
Section: Introductionmentioning
confidence: 99%
“…Children with AR, similar to those with non-AR, are known to develop rhinitis symptoms in response to nonallergenic irritants, such as cold air, high air pollution, weather change, cigarette smoking, perfume, hair spray, mold odors, bleach, cosmetics, and other substances 22. Therefore, we performed this study for 3 months, during only 1 season, to reduce the effects of non-allergenic irritants and other factors, such as weather changes, that can act as confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Children with nonallergic rhinitis are known to experience milder nasal signs and/or symptoms, and nonallergic rhinitis takes a less severe clinical course than allergic rhinitis [ 19 - 21 ]. Signs and/or symptoms of nonallergic rhinitis seem to be transient, while those of allergic rhinitis persist; this disparity increases with age [ 15 ].…”
Section: Clinical Manifestation Of Nonallergic Rhinitis In Childrenmentioning
confidence: 99%
“…This phenotype has a multifactorial etiology that is triggered by cold air, particulate matter, and nonspecific chemicals. Links to irritant exposures including air pollution and secondary cigarette smoke were also reported in children [ 19 , 22 , 37 ]. Moreover, they induce a non–IgE-mediated inflammatory response and hyper-reactivity to mucosal components or neural innervations of the nose [ 36 ].…”
Section: Idiopathic Rhinitismentioning
confidence: 99%